Grey relational analysis and fuzzy synthetic discrimination of antioxidant components in peach fruit - Zhang, Binbin; Shen, Zhijun; Ma, Ruijuan; Yan, Juan; Yu, Mingliang (Archives of Biological Sciences, 2018)
Paper description: Previous studies have revealed the close correlation between the phenolic compound content and oxidation resistance of fruits. Both grey relational analysis and fuzzy synthetic discrimination has seldom been used to evaluate the overall oxidation resistance in fruits. These methods were used to select peach varieties with high oxidation resistance. The indicators of individual phenolic content and the total content of phenols during fruit development in three types of peach with different flesh color were combined. This provides a new avenue for the study of overall resistance to oxidation in fruits. Abstract: Free phenolic compounds and total phenolic content were quantified using four stages of four blood-flesh and four non-blood-flesh peach fruits. Data were used to assess the oxidation resistance using grey relational analysis and fuzzy synthetic discrimination methods. Data from equal-weight and weighted evaluations calculated using both grey relational analysis and fuzzy synthetic discrimination were very similar. The weighted relational grade and weighted evaluation value of the overall resistance to fruit oxidation were ordered according to the weight coefficient method, which demonstrated that there were discrepancies in the ranking of oxidation resistance of the tested varieties between early and late fruit developmental stages. During fruit development, the blood-flesh varieties showed a relatively high overall resistance to oxidation, with the highest observed in Beijingyixianhong. The results suggest that both grey relational analysis and fuzzy synthetic discrimination have high applicability in assessing the resistance to oxidation of peach varieties. https://doi.org/10.2298/ABS171209005Z Received: December 9, 2017; Revised: January 19, 2018; Accepted: January 30, 2018; Published online: February 9, 2018 How to cite this article: Zhang B, Shen Z, Ma R, Yan J, Yu M. Grey relational analysis and fuzzy synthetic discrimination of antioxidant components in peach fruit. Arch Biol Sci. 2018;70(3):…